Optimizing perovskite LEDs and tandem PV cells: The role of photon-recycling and luminescent coupling in presence of strong light scattering - Simon J. Zeder; Balthasar Blülle; Beat Ruhstaller; Urs Aeberhard (APL Energy)
Photon recycling (PR) in light-emitting and light-absorbing devices with incoherent scattering is investigated using a novel optical framework, self-consistently coupled to electrical models for current- and voltage-controlled devices to trace the inherent optoelectronic backcoupling associated with PR. This study reveals a universal competition between photon re-absorption and scattering processes, which governs performance across device types. In light-emitting diodes, the optimal emitter layer thickness is highly sensitive to scattering outcoupling structures and PR; their consideration in modeling is crucial. In addition, scattering structures impose stricter radiative efficiency requirements for PR to remain beneficial, highlighting the trade-off between loss mitigation and re-absorption penalties. For photovoltaic devices, the impact of front texturing on PR and luminescent coupling (LC) in perovskite–silicon tandem solar cells is quantified, including the first demonstration of luminescent self-coupling at the emissive perovskite-coated texture. While the texture minimally affects PR/LC overall, both scattering and re-absorption redistribute photogeneration. LC enhances tandem efficiency by 4.4%abs in the Auger limit for bottom-limited configurations, illustrating how photon redirection alleviates current-matching constraints.